MO151: A Randomized Controlled Trial of Sodium Zirconium Cyclosilicate Versus Standard of Care for Hyperkalaemia in Chronic Kidney Disease: Phase 4 Continuity Study Design and Rationale. (3rd May 2022) - Burton, James; Allum, Alaster; Amin, Alpesh; Linde, Cecilia; Lesén, Eva; Eudicone, James; Sood, Manish
Abstract: BACKGROUND AND AIMS: Individuals hospitalized with hyperkalaemia (HK) and chronic kidney disease (CKD) are at very high risk of HK recurrence, which often requires hospital re-admission [1]. Recurrent HK events have a significant impact on healthcare resource utilization (HCRU) and costs [2]. Several approaches, such as reduction in dietary potassium (K + ), reduction or discontinuation of diuretic and renin-angiotensin-aldosterone system inhibitor (RAASi), or oral K + binders may be used to manage HK in the outpatient setting. Sodium zirconium cyclosilicate (SZC) is an orally administered, non-absorbed, highly selective K + binder approved for the treatment of HK in adults. In phase 3 trials, after achieving normokalaemia (NK), individualized once-daily SZC therapy maintained normal range serum K + levels for up to 1 year in adult outpatients [3]. However, it is unknown if SZC prevents HK recurrence compared with standard of care (SoC). Here, we present the rationale and design of the phase 4 CONTINUITY study (D9480C00023), which will compare the efficacy of continued SZC treatment, as part of the post-discharge medication regimen, with SoC, in maintaining NK and reducing HK-related hospital admissions and emergency department (ED) visits. METHOD: CONTINUITY is a randomized controlled, open-label, parallel-group, multicentre study in participants with CKD treated for HK while in hospital, to be conducted in 30–50 study sites across four to seven European countries. The study will comprise both an in-hospital and an outpatient (post-discharge) phase (Figure ). During the in-hospital phase, all participants will be treated with SZC to correct HK (SZC 10 g three times daily, up to 72 h) and maintain NK (SZC from 5 g every other day to 10 g once daily) as per local label for 2–14 days. At discharge, participants with NK established on an SZC maintenance dose will be randomised (1:1) to either SZC per local label (Arm A) or SoC per local practice (Arm B); participants intended to be discharged with a K + binder will not be randomized and will be discontinued from the study. Following randomization, participants enter the outpatient phase and will be monitored for 180 days post-discharge via seven planned follow-up visits or phone calls, followed by a site visit at 7 days after end of treatment (Figure ). Participants will be screened to yield 506 entering the in-hospital phase, resulting in 430 participants discharged and randomized (215 per arm) and 344 evaluable participants. Adults (≥18 years) with stage 3b–5 CKD or eGFR <45 mL/min/1.73 m 2 at or within 3 months prior to study screening, who are admitted to hospital with a serum K + of 5.5–6.5 mmol/L, will be eligible. The primary endpoint is the occurrence of NK (serum K + 3.5–5.0 mmol/L) at 180 days post-discharge. Secondary and exploratory outcomes assessed within 180 days post-discharge include a composite endpoint of any HK-related hospital admission or ED visit, use of rescue therapy for HK and all-cause death, as well as RAASi treatment status and dose, and K + level. Safety and tolerability will also be evaluated. CONCLUSION: CONTINUITY is the first study to examine the efficacy of extended use of a novel K + binder post-discharge compared with SoC, on the maintenance of NK and reduced HCRU among patients with HK, with CKD stage 3b–5. This study will address the importance of maintaining NK after discharge in routine clinical practice, and the impact of improved management of patients with CKD and HK.